The scientific problems of peridization of the history of state and law of Ukraine - Ухач, Василь Зіновійович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2011)
In this article analyzes the scientific approaches to periodization of the history of state and law of Ukraine. Author concludes that auters went about silently the approaches and principles of creation of periodization or a identifying different approaches that give nearly identical periods list. Only science-based distribution of historical and legal material will see the basic laws of state and legal specifics of the country.